Additively Manufactured Polymers for Electronic Components - Filippo Iervolino; Raffaella Suriano; Marco Cavallaro; Laura Castoldi; Marinella Levi (Applied Sciences)
Over the last decade, polymers have attracted increasing attention for the fabrication of electronic devices due to the innovative results that can be achieved using additive manufacturing (AM) processes. Intrinsically conductive polymers are commonly used to obtain flexible and stretchable devices. They also enable the customisation of electronic devices when processed through AM. However, their main limitation is the reduction in electrical conductivity under mechanical deformation, such as bending. Extrinsically conductive nanocomposites, incorporating conductive fillers into polymer matrices, demonstrate the ability to retain electrical conductivity even following repeated bending, presenting a promising solution to the limitations of intrinsically conductive polymers. However, a gap remains in optimising their processing conditions for diverse 3D printing technologies. Moreover, fillers should be carefully selected according to the application’s specific needs. Dielectric polymers are also very promising for various electronic applications, but they are less investigated and have lower visibility than their conductive counterparts. This review presents three classes of polymer materials, i.e., intrinsically and extrinsically conductive polymers and insulators, discussing their advantages, drawbacks, and applications for 3D printing in electronics. This overview concludes with assessing future investigation areas needed to unlock the possibilities of 3D-printed polymers in electronics.